2005
DOI: 10.1007/s10681-005-4316-y
|View full text |Cite
|
Sign up to set email alerts
|

Bulked segregant analysis to detect main effect QTL associated with grain quality parameters in Basmati 370/ASD 16 cross in rice Oryza sativa L) using SSR markers

Abstract: In the present study a population consisting of 247 F 2 individuals from the cross between Basmati 370, a superior quality basmati variety and ASD16, a non-basmati high-yielding variety was analyzed for their segregation pattern of grain length (GL), grain breadth (GB), cooked grain length (CGL), cooked grain breadth (CGB), and gelatinization temperature (GT). Except GT, all other traits showed normal distribution indicating the polygenic control over the traits. The correlation analysis between traits indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…Yano and Sasaki (1997) suggested that rice grain quality is under the inXuence of quantitative alleles showing continuous variation. Earlier genetic investigations reported monogenic (Chao 1928;Ramaiah et al 1931), digenic (Bollich 1957) and trigenic (Ramiah and Parthasarathy 1933) inheritance for grain length besides polygenic inheritance for grain length and breadth (Jones et al 1935;Chang 1974), but the results are inconclusive and limited (Govindaraj et al 2005). Cooking quality of rice can be attributed to three major grain properties viz., grain elongation, volume expansion and water absorption (Ge et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yano and Sasaki (1997) suggested that rice grain quality is under the inXuence of quantitative alleles showing continuous variation. Earlier genetic investigations reported monogenic (Chao 1928;Ramaiah et al 1931), digenic (Bollich 1957) and trigenic (Ramiah and Parthasarathy 1933) inheritance for grain length besides polygenic inheritance for grain length and breadth (Jones et al 1935;Chang 1974), but the results are inconclusive and limited (Govindaraj et al 2005). Cooking quality of rice can be attributed to three major grain properties viz., grain elongation, volume expansion and water absorption (Ge et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier genetic investigations reported monogenic (Chao 1928;Ramaiah et al 1931), digenic (Bollich 1957) and trigenic (Ramiah and Parthasarathy 1933) inheritance for grain length besides polygenic inheritance for grain length and breadth (Jones et al 1935;Chang 1974), but the results are inconclusive and limited (Govindaraj et al 2005). Cooking quality of rice can be attributed to three major grain properties viz., grain elongation, volume expansion and water absorption (Ge et al 2005). It is determined by the physicochemical properties of the endosperm viz., amylose content (AC) (Webb 1980;Juliano 1985), gel consistency (GC) (Cagampang et al 1973) and gelatinization temperature (GT) (Little et al 1958).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, for GWM182, 5 of 10 individuals possessed tolerant bulk profiles (Figure 2). Some studies have reported using BSA to find links for specific genes (Michelmore et al, 1991;Govindaraj et al, 2005). One-way ANOVA was carried out using marker genotypes as groups.…”
Section: Resultsmentioning
confidence: 99%
“…This technique was successfully used to identify DNA markers linked to the downy mildew resistance gene in lettuce (Michelmore et al, 1991), leaf rust resistance in barley (Poulsen et al, 1995), malaria and nematode resistance genes in mosquitoes (Severson et al, 1999), powdery mildew resistance gene in wheat (Chantret et al, 2000), sex determination in aphids (Gadau et al, 2001), vaccine response in chicks (Kaiser et al, 2002), QTL for grain quality in rice (Govindaraj et al, 2005), sex expression in shrimps (Khamnamtong et al, 2006), genetic mapping in zebra fish (Bradley et al, 2007), clubroot resistance genes in oilseed rape (Werner et al, 2008), red wing patterning in Heliconius butterflies (Baxter et al, 2008), isolation of sex-linked SCAR markers in yellow catfish (Wang et al, 2009), and powdery mildew resistance gene in soybean (Kang & Mian, 2010).…”
Section: Introductionmentioning
confidence: 99%